The Integration Perspectives for Historical Study of Indonesian Islam - Abdurahman, Dudung (TAWARIKH, 2017)
ABSTRACT: During 15 centuries, Islam has always met with many cultures, even Moslems who come from different ethnic and social backgrounds have made Islam a multicultural reality. Therefore, the paradigm of humanity science will be always actual to understand the reality of Islamic society in the context of the integration amongs historical religious and cultural perspectives. The three perspectives can become on epistemology of "multicultural Islam". Its methodology can be developed into a variety of Islamic objects. In this paper, the epistemology will be more focused on history and culture. Both are explored in a religious context of Islam. The use of this perspective is based on the development of Islam in Indonesia and Sufism on local communities in particular. As an outline of the development, as follow: firstly, the development of Islam always adapts to the local culture; secondly, ongoing local Islamic construct and it is also changing due to the influence of Western culture and the reform in the Islamic world; and thirdly, continuing encounters of contemporary Islamic diversity, due to the development of modern multiculturalism. In addition, the integration of perspectives in explaining Islam can produce knowledge of "historical-multicultural", that is Islam in reality, difference, and diversity that occurs and is recognized by the Moslem communities within a certain time. Furthermore, the knowledges based on "historical-multicultural" can also be used as a discourse for solving human problems that always arise in the present and future days. KEY WORDS: Historical Study; Religious and Cultural Perspectives; Indonesian Islam; Multicultural Islam; Islamic Epistemology.About the Author: Prof. Dr. Dudung Abdurahman is a Lecturer at the Faculty Adab and Humanities UIN (Universitas Islam Negeri or State Islamic University) Sunan Kalijaga, Jalan Marsda Adisucipto, Yogyakarta, Indonesia. For academic interests, the author is able to be contacted via e-mail at: durahman.uin@gmail.comRecommended Citation: Abdurahman, Dudung. (2017). âThe Integration Perspectives for Historical Study of Indonesian Islamâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.9-22. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Article Timeline: Accepted (August 17, 2017); Revised (September 19, 2017); and Published (October 28, 2017).